ASSESSMENT OF FADAMA BENEFICIARIES’ ATTITUDE TO UPTAKE OF CASSAVA PRODUCTION TECHNOLOGIES IN OSUN STATE, NIGERIA - ADELEKE, A.; ADESOJI, A. S. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
The study assessed the attitude of Fadama III Additional Financing Project beneficiaries towards the uptake of improved cassava production technologies in Osun State. A proportionate sampling technique was used to select four Local Government Areas (LGAs) from Osogbo and two from Iwo Zones. Proportionate and systematic random sampling techniques were used to select 160 beneficiaries from 535 in Osogbo and 80 from 268 beneficiaries in Iwo zones. Data were collected on beneficiaries’ socio-economic characteristics and their attitude towards the uptake of improved cassava production technologies. Data were analyzed using percentages, means, Chi-square, and correlation analytical tools. The results show that beneficiaries had favorable attitudes towards five of the 12 technologies while they had indifferent attitudes towards the other seven of the technologies disseminated by the Fadama III+AF Project.  Furthermore, nine of the 12 cassava production technologies disseminated by the Fadama III+AF Project had high uptake levels while the remaining three had low uptake levels. Further results show that socio-economic characteristics like age (r=0.128), cassava farm size (r=0.162), and Fadama group membership (r=0.230) were positively and significantly correlated with uptake of cassava production technologies at p≤0.05 and p≤0.01 respectively. Also, non-parametric variables like sex (c2=10.417), religion (c2=111.600), and marital status (c2=497.500) had a significant association with the uptake of cassava production technologies. It was concluded that the beneficiaries’ attitude towards the uptake of cassava production technologies disseminated by Fadama III+AF was favorable and high among respondents in Osun State.